Mitigating the harm caused by Pseudomonas aeruginosa in Cystic Fibrosis - Palser, Sally C. (2024)
Cystic fibrosis (CF) affects up to 100,000 people worldwide. Defects in the Cystic Fibrosis Transmembrane Regulator (CFTR) gene cause abnormally viscid secretions at epithelial surfaces. In the lungs the abnormal secretions reduce clearance of both pathogens and sputum, predisposing to recurrent lung infections. Ultimately recurrent infections can cause respiratory failure and death.